TANDA TANGAN ELEKTRONIK DALAM KONTRAK BISNIS INTERNASIONAL - Tamara Mutiara Ramadani; Rizka Nurliyantika (SOL JUSTICIA, 2022)
An international business contract is a common guideline for the parties to bind themselves to certain rights and obligations across national boundaries. These guidelines are usually closely related to trade transactions, which at present can be carried out remotely or electronically. The process of electronic commerce was a means of transactions without face-to-face between buyers and sellers until the emergence of electronic signatures. The institution that until now has played a role in harmonizing the law of electronic commerce transactions is the United Nations Commission on International Trade Law (UNCITRAL), which is a subsidiary organ of the United Nations (UN). Special arrangements for electronic signatures internationally are found in the UNCITRAL Model Law on Electronic Commerce 1996 and the UNCITRAL Model Law on Electronic Signature 2001. Judging from the formation of these international regulations, this indicates that the international community is in dire need of regulations that are by technological developments, especially in the field of transactions. - international trade transactions. This study uses secondary data collected through the literature study method. The issue raised is how international contract law regulates electronic signatures and how is the legal protection for users of electronic signatures. From these two questions, it was found that the two Model Laws from UNCITRAL were not binding on the state. The state is free to follow the entire contents of the rules, in part, or even reject the whole. Model Law is a guideline to assist countries in making their national laws. Furthermore, the rules made by the ICC, ICSID, and UNCITRAL are believed to be able to solve problems related to international business contracts, including the topic of electronic signatures. Although the Model Law has also discussed how electronic signatures can apply to support electronic commerce.